2016
DOI: 10.13057/nusbiosci/n080223
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cassava starch-based edible film enriched with lemongrass oil (Cymbopogon citratus)

Abstract: Abstract. Resianingrum R, Atmaka W, Khasanah LU, Kawiji, Utami R, Praseptiangga D. 2016. Characterization of cassava starchbased edible film enriched with lemongrass oil (Cymbopogon citratus). Nusantara Bioscience 8: 278-282. Good packaging is necessary to prevent food spoilage before and after processing. The edible film maintains food quality and an eco-friendly packaging. Cassava starch-based edible film is capable of being developed because of the approaching appearance of plastic packaging. The addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
(3 reference statements)
1
12
0
Order By: Relevance
“…This showed that the film containing oregano EOs had higher value of tensile strength than the film that contained neem EOs. The better film that represented a novel and good alternative for use in food packaging was the film that contained oregano EOs [ 1 ].…”
Section: Starch-based Polymer Film Incorporated With Antimicrobialmentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that the film containing oregano EOs had higher value of tensile strength than the film that contained neem EOs. The better film that represented a novel and good alternative for use in food packaging was the film that contained oregano EOs [ 1 ].…”
Section: Starch-based Polymer Film Incorporated With Antimicrobialmentioning
confidence: 99%
“…Food packaging can prevent food damage [ 1 , 2 , 3 , 4 , 5 , 6 ]. It is essential to select the proper materials and packaging techniques to retain food quality and freshness [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The edible films were prepared according to Resianingrum [22] with a few modifications. Briefly, 5 grams of millet starch were dissolved in 150 mL of distilled water.…”
Section: Preparation Of the Starch Edible Filmmentioning
confidence: 99%
“…The results showed that oregano essential oil improved the oxidative stability of microencapsulated fish oil. Most researchers have reported the preparation of active packaging material based on starch and essential oils through the solvent casting process . However, only few researchers have described the use of extrusion to prepare active packaging based on starch and essential oil, although extrusion is an important method for processing active packaging on an industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers have reported the preparation of active packaging material based on starch and essential oils through the solvent casting process. [18][19][20] However, only few researchers have described the use of extrusion to prepare active packaging based on starch and essential oil, although extrusion is an important method for processing active packaging on an industrial scale. In this work, oregano essential oil (OEO) was microencapsulated in sodium alginate through gelling process.…”
Section: Introductionmentioning
confidence: 99%